HMGB1 as a Potential Therapeutic Target for Neuropathic Pain - Takehiko Maeda; Masanobu Ozaki; Yuka Kobayashi; Norikazu Kiguchi; Shiroh Kishioka (Elsevier, 2013)
Neuropathic pain, which is intolerable and persistent, arises as a direct consequence of a lesion or disease affecting the somatosensory system and can be debilitating for the affected patients. Accumulating evidence from animal studies has revealed the potential molecular basis for neuropathic pain, resulting in many promising therapeutic targets. While efforts at drug discovery have been made, conventional pharmacotherapy, including the use of opioid analgesics, is still insufficient for the relief of neuropathic pain. Therefore, novel target molecules that may lead to the development of promising analgesics are eagerly anticipated for improved treatment of neuropathic pain. In various insults such as sepsis and ischemia, high-mobility group box 1 (HMGB1) is released extracellularly to induce inflammation. HMGB1 was originally identified as a ubiquitous nuclear protein, but emerging evidence has suggested that HMGB1 also plays a role in neuroinflammation as a pro-inflammatory mediator. These findings suggest that HMGB1 may be involved in the pathology of neuropathic pain. In fact, some reports demonstrate an involvement of HMGB1 in the development and maintenance of neuropathic pain in experimental animals. Here, we overview the characteristics of HMGB1 as a pro-inflammatory mediator and show the promise of HMGB1 as a therapeutic target for neuropathic pain. Keywords:: HMGB1, neuropathic pain, neuroinflammation, pro-inflammatory cytokine, nucleokine